Bentuk Ruang Terbuka pada Permukiman Tepian Sungai Musi, Palembang - Maya Fitri Oktarini; Husnul Hidayat; Klarissa Susanto; Afzal Abilais (Program Studi Arsitektur Fakultas Teknik Universitas Sriwijaya, 2022)
Public open space is an important residential facility to create a healthy living space for city residents. Facilities that perform a major role in accommodating the activities of community life in urban settlements. In riverside settlements, riverbank areas have a large land potential for building public open spaces. The riverside open space is an important element in making the characteristics of a riverside city. This study aims to identifies the form, distribution, and size of open space in settlements along the Musi riverbank of Palembang. This study also observes the function of open space in accomodating residents’ activities. The research uses rationalistic methods, through field observations in the form of observations of physical settings and functional aspects. The results show that the open space for public interaction and activities is evenly distributed in various sizes and locations, but is not supported by supporting facilities. Meanwhile, the community creates alternative open spaces to accommodate their various activities for the solution of lacking public space. Without an opening of new land, revitalization of the settlement infrastructure should be focus on improve the informal open spaces by providing a sitting area with benches, lighting, shade, trees, and stall area could increase comfortability, safety, and leisurity of the public open space.